Architectural tradition and modernity as crypto‐colonial ways of seeing: A comparison of Kathmandu's 1934 and 2015 post‐quake reconstructions. Issue 8 (16th July 2019) - Nelson, Andrew
Abstract: This essay compares the architectural responses to Kathmandu's 1934 and 2015 earthquakes through a postcolonial framework. While rulers and elites used post‐1934 reconstruction to impose their notion of modernity upon the city, in post‐2015 reconstruction, conservationists see an opportunity to remake the traditional city. Instead of framing modernity and tradition as opposing forces, however, this essay reconsiders references to both as markers of class distinction that obscure Nepal's enduring crypto‐colonial position.